987 Emipediology and Morbidity of Late Preterm Neonates in Correlation with Maternal Risk Factors in Hessen, Germany. (October 2012) - Faas, D; Vajz, M; Hennewig, U; Misselwitz, B; Oehmke, F; Heckmann, M
Abstract : Short and long term morbidity in late preterm neonates (LP) and their correlation to maternal risk factors are relevant as shown in multiple studies in North America and European countries. Epidemiological studies showed an increase in LP birth over time. Corresponding data for Germany have not yet been published. Our goal was to evaluate the epidemiology of LP over a 7 year period and the correlation to potential maternal risk factors in Hessen, Germany. Data was collected from the perinatal und neonatal quality assurance in Hessen form 2001 to 2007. For some calculations the two data sets were merged. Overall the data sets of 360.000 births and 44.000 neonatal hospitalizations were available, which is about 7.5% of all births during that period in Germany. There is no increase in LP births from 2001 to 2007 in Hessen. Neonatal short term morbidity of LP is within the expected range and significantly higher than in term neonates. The following maternal risk factors were more predominant in LP: placental insufficiency, gestational diabetes, obesity, arterial hypertension, artificial reproduction techniques, caesarian section in previous pregnancy, ethnic background and multiple births. Maternal morbidity has an influence on the short term morbidity of LP. There has been no increase in late preterm births in Hessen Germany 2001–2007. Several maternal risk factors for late preterm births can be identified. These results could be used to optimize management of mothers at risk to reduce the number of late preterm births and neonatal morbidity.